Optimización de la gestión de inventario de la empresa Pulpamol S. A. - Alvarracin Escobar, Celso Tobias (2023)
This research work is carried out with the objective of optimizing the inventory management of spare parts and maintenance supplies of the company PULPAMOL S.A. dedicated to the manufacture of egg trays with recycled material, due to the low level of inventory management, lack of manipulable information and spare parts and supplies acquired without the guidance of a methodology, which is causing unplanned shutdowns of prolonged time. This research work is developed using the descriptive methodology that allows describing and characterizing the progress of the research work which is presented to optimize the inventory control and management of the acquisition of spare parts and supplies. The structure of this work has three phases divided into the collection of information, manipulation, control of digital data entry and the development of two methodologies to highlight the need for the acquisition of spare parts and important inputs. In the first phase the inventory is improved by including spare parts and supplies that have not been taken into account through the collection of information, the second phase improves the inventory control allowing to search and manipulate the collected data, in addition, it allows to differentiate in a unique way the spare parts and supplies through the development of a codification and finally the third phase has the improvement of the inventory in terms of monitoring through a drop-down window that allows the introduction of information, in addition, the ABC classification is developed, which is focused on the demand and annual costs of each spare part and input that influence the maintenance activity within the company, thus obtaining a control of the spare parts with greater, medium and lesser importance either by demand and costs that are needed, the EOQ methodology with safety stock that allows to know the optimal order quantities of the most relevant spare parts and inputs, additionally UNIVERSIDAD TÉCNICA DE COTOPAXI - CARRERA DE INGENIERÍA INDUSTRIAL 5 the quantity in stock of each spare part and input with relevant importance is known, which prevents long duration stops with an estimated annual time. Therefore, the optimization of the company's inventory management is developed taking into account the existing annual stops that are a total of 5 weeks, having an average cost of $ 236,880.00 in economic and productive losses for the company, with the development of the different phases, it is intended that the company saves a total of $ 135,360.00 annually, free of acquisition costs of spare parts and supplies, this saving will be achieved thanks to the collection of information and application of methodologies which allows the company a better management of spare parts and supplies of great importance. It is concluded that, through the collection of information, categorization, development of methodologies and drop-down window, the company will generate less economic losses by having knowledge of the necessary values of spare parts orders and digitized and relevant information of the same that the machinery needs for its operation.